IDENTIFIKASI PARASIT USUS DAN SEL DARAH PADA FESES BALITA GIZI BURUK DI MULYOREJO KECAMATAN TIRTO KABUPATEN PEKALONGAN - Tuti Suparyati (LPPM Universitas Pekalongan, 2020)
Nutrients come from food consumed through the digestion process such as absorption, transportation, storage and metabolism. Malnutrition during the golden age (under five years old) is irreversible, malnutrition affects brain development.Malnutrition caused by less consumption of food and infectious diseases. Intestinal infection by parasites is one of the types of infectious diseases in toddlers that can cause malabsorption of nutrients and reduce appetite. In addition, intestinal infections can also cause injury, so that blood cells are obtained in the feces. These all increase the risk of malnutrition.This research aim to find intestinal parasitic infection and blood cells in malnourished toddlers in Mulyorejo, Tirto District, Pekalongan Regency.The research method is descriptive, to describe the results of feces examination, data collection by feces examination in the laboratory, using the direct method and centrifugation to get intestinal parasites. The population in this research were all malnourished toddlers in Mulyorejo in August 2019 with 8 of total respondents. For sample using total sampling of all respondents.The results is intestinal parasitic infections were not found in 8 samples tested, intestinal protozoa 0 (0%) and intestinal worms from group soil transmitted helminth 0 (0%). Examination of blood cells, found 2 feces samples (25%) contain with normal leukocytes and 6 samples (75%) exceeded from normal limits. Other than that, 0 feces samples (0%) with normal erythrocytes and 8 samples (100%) exceeded from normal limits.The conclusions of this research is intestinal parasitic infections such as intestinal protozoa 0 (0%) and intestinal worms 0 (0%) were not found in 8 samples tested, but blood cells were present with exceeded from normal limits.